Pathology Bureaucracy: Reality of the Indonesian Bureaucracy and Prevention (Jurnal Bina Praja, 2017)
The performance of a bad bureaucracy indicates a bureaucracy is riddled with problems; a pathology which arose not always coming from outside the bureaucratic body, but pathology that has been flourishing and will be exerting influence when the bureaucracy is unhealthy. This research article would like to give an overview of the incidence of the pathological bureaucracy which argumentation pathology can prevent. The phenomenon occurs that the bureaucracy could not deliver good public services and bureaucracy is a den of disease. The specific purpose of this research is focused on finding ways of preventing the pathology of the bureaucracy that comes from a variety of scientific literature. The method in this research article is systematic reviews technique that tries to identify all the written evidence exists regarding research themes. The results of this study reveal that the pathology of the bureaucracy is something to be prevented if we want the bureaucracy to run the task properly, one of the ways that can be done is to do a bureaucratic innovation (an innovation on structure, systems, culture). The innovation of bureaucracy will not only make changes to the organization to prevent the pathology of the bureaucracy but also as an ingredient to do discretion for a government policy especially regional government.